Glass–iron oxide, glass–iron and glass–iron–carbon composite hollow particles with tunable electromagnetic properties. Issue 34 (11th August 2016) - An, Zhenguo; Zhang, Jingjie
Abstract : Stepwise combustion–calcination route to low-density glass–iron oxide, glass–iron and glass–iron–carbon composite shelly hollow particles with tunable electromagnetic property. Abstract : Composite shelly hollow particles with glass–iron oxide, glass–iron and glass–iron–carbon shells were prepared on a large scale through a stepwise strategy involving sol combustion assembly and controlled heat treatment. Micron-sized silicate glass hollow particles prepared in our previous work were used as the starting material to serve as the first shell with hollow interior. Then iron oxide and iron–carbon shells were assembled on the silicate glass shell by fast dehydration–combustion of a mixed sol containing iron resource, fuel and the preformed glass hollow particles in air and nitrogen atmospheres, respectively. Afterwards, the glass–iron oxide composite shelly hollow particles underwent a thermal reduction treatment to get metallic iron shells. The electromagnetic properties of the composite shelly hollow particles were studied and the results demonstrate that they present ferromagnetic properties and tunable microwave-absorbing performances related to the composition of the ferruginous shells. Owing to the synergism of appropriate magnetic and dielectric losses and enhanced interfacial effects, the glass–iron–carbon composite shelly hollow particles possess the best microwave-absorbing performance, in terms of both the minimum reflection loss (RL) value and the effective bandwidth, among the three kinds of products. Moreover, the as-obtained samples possess ultra-low density of 0.44, 0.46 and 0.51 g cm −3, respectively, for the glass–iron oxide, glass–iron and glass–iron–carbon composite shelly hollow particles, and may be promising candidates as low-density magnetic materials and microwave absorbents.